Adult response to olanzapine or clozapine treatment is altered by adolescent antipsychotic exposure: A preclinical test in the phencyclidine hyperlocomotion model. (April 2014) - Shu, Qing; Hu, Gang; Li, Ming
This study examined how repeated olanzapine (OLZ) or clozapine (CLZ) treatment in adolescence alters sensitivity to the same drug in adulthood in the phencyclidine (PCP) hyperlocomotion model. Male adolescent Sprague-Dawley rats (postnatal day (P) 44–48) were first treated with OLZ (1.0 or 2.0 mg/kg, subcutaneously (sc)) or CLZ (10.0 or 20.0 mg/kg, sc) and tested in the PCP (3.2 mg/kg, sc)-induced hyperlocomotion model for five consecutive days. Then a challenge test with OLZ (0.5 mg/kg) or CLZ (5.0 mg/kg) was administered either during adolescence (~P 51) or after the rats matured into adults (~P 76 and 91). During adolescence, repeated OLZ or CLZ treatment produced a persistent inhibition of PCP-induced hyperlocomotion across the five test days. In the challenge test during adolescence, rats previously treated with OLZ did not show a significantly stronger inhibition of PCP-induced hyperlocomotion than those previously treated with vehicle (VEH). In contrast, those previously treated with CLZ showed a weaker inhibition than the VEH controls. When assessed in adulthood, the enhanced sensitivity to OLZ and the decreased sensitivity to CLZ were detected on ~P 76, even on ~P 91 in the case of OLZ. These findings suggest that adolescent OLZ or CLZ exposure can induce long-term alterations in antipsychotic response that persist into adulthood.